2019
DOI: 10.15403/jgld-524
|View full text |Cite
|
Sign up to set email alerts
|

Transduodenal EUS FNA Diagnosis of Idiopathic Retroperitoneal Fibrosis

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Lastly, our patient also developed a possibly IgG4-related cholangitis and peritoneal fibrosis during treatment. However, this latter diagnosis was not supported by histology since the risk of bleeding related to the sampling of peritoneal fibrosis was unbalanced regarding the benefits, even with an EUS approach [27]. Moreover, data from a previous series [28] of retroperitoneal fibrosis patients showing that inflammatory retroperitoneal fibrosis is frequently not extended below the aortic bifurcation and causing medial ureteral attraction, similar to our case, also supported our decision not to attempt any sampling.…”
Section: Discussionmentioning
confidence: 43%
“…Lastly, our patient also developed a possibly IgG4-related cholangitis and peritoneal fibrosis during treatment. However, this latter diagnosis was not supported by histology since the risk of bleeding related to the sampling of peritoneal fibrosis was unbalanced regarding the benefits, even with an EUS approach [27]. Moreover, data from a previous series [28] of retroperitoneal fibrosis patients showing that inflammatory retroperitoneal fibrosis is frequently not extended below the aortic bifurcation and causing medial ureteral attraction, similar to our case, also supported our decision not to attempt any sampling.…”
Section: Discussionmentioning
confidence: 43%
“…However, we herein showed that the endoscopic arena is likely to also play a significant role in this setting, which could be even preferred over other modalities. Although isolated reports, that share our positive experiences, exist [17,18,19], EUS-FNA/FNB as a modality for diagnosing RPF has attracted surprisingly little attention in the literature. ▶ Table 1 provides an overview over previously published case reports that demonstrated the use of EUS-FNA/FNB to successfully diagnose RPF.…”
Section: Discussionmentioning
confidence: 99%